Pengaruh Penambahan Volume Air dalam Cat Akrilik Terhadap Kualitas Warna Suminagashi Pada Scarf Polyester - Rizki Laillatul Zakiyah; Ma’rifatun Nashikhah (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Suminagashi is a technique for decorating fabric or paper by dropping ink or paint onto the surface of water or a water-gelmixture, then placing the fabric or paper on the liquid so that the color is absorbed. The study aims to examine the effect of increasing water volume in acrilylic paint on the color quality of the suminagashi technique appiled too polyester scraves, specifially in terms of color sharpness and color absorption. Additionally, it investigates the variations in color outcomes across different water-to-point ratios. An experimental method was employed using three paint-to-water ratios 1:1, 1:2, and 1:3. Color quality was evaluated through observations by 30 respondents and analyzed using the Kruskal-Wallis H test with SPSS version 30. The result indicate that the volume of water in the acrylic paint mixture significantly influences color quality. The 1:1 ratio produced the higest color sharpness, while the 1:3 ratio showed the best color absroption. Distinct color differences were observed among the scarves produced with each ratio.